Laser Ablative Structural Modification of Poly(ethylene-alt-maleic anhydride) - Masoudi, Husain M. (2003)
Pulsed IR laser ablation of poly(ethylene-alt-maleic anhydride) results in the deposition of polymeric films possessing the same ratio of anhydride and -CH2- groups and represents a very rare example of laser ablative deposition of polymeric films that are structurally identical to the ablated polymer. This process differs from the conventional thermolysis of poly(ethylene-alt-maleic anhydride) that is controlled by expulsion of CO2 and CO and yields a nonpolar polymeric residue. The IR laser ablation of poly(ethylene-alt-maleic anhydride) in sodium metasilicate affords deposition of polymeric films containing carboxylate (-CO2-) groups. This process is the first example of reactive ablation in which the deposited polymeric film incorporates constituents of two different species exposed to laser radiation.